PENDEKATAN CLIENT CENTERED DENGAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN PERCAYA DIRI SISWA DARI PERGAULAN TEMAN SEBAYA - Veninda Herinawati; Masturi Masturi; Richma Hidayati (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
Lack of self-confidence in a person usually arises because of fear, anxiety, worry, and lack of confidence in the abilities that exist in themselves. Someone who has a lack of self-confidence will show different behavior from people in general, such as unable to do much, shy, inferior, and always doubtful in carrying out their duties, not daring to speak in public, so they need support from others. The problem in this research is how the BK teacher overcomes the lack of self-confidence from peer association in the VIII grade of SMP 4 Kudus. Self-confidence can be interpreted as a belief in one's own abilities that are adequate and aware of their abilities and can use them appropriately, so as not to harm others.On the other hand, people who lack self-confidence have a negative self-concept, lack confidence in their abilities, and therefore lack of self-confidence needs to be increased to become confident. This research uses a case study qualitative research method, which is a form of research based on human understanding and behavior based on human opinion, and the research subjects can be individuals or groups.Lack of self-confidence in a person usually arises because of fear, anxiety, worry, and lack of confidence in the abilities that exist in themselves. Someone who has a lack of self-confidence will show different behavior from people in general, such as unable to do much, shy, inferior, and always doubtful in carrying out their duties, not daring to speak in public, so they need support from others. The problem in this research is how the BK teacher overcomes the lack of self-confidence from peer association in the VIII grade of SMP 4 Kudus. Self-confidence can be interpreted as a belief in one's own abilities that are adequate and aware of their abilities and can use them appropriately, so as not to harm others.On the other hand, people who lack self-confidence have a negative self-concept, lack confidence in their abilities, and therefore lack of self-confidence needs to be increased to become confident. This research uses a case study qualitative research method, which is a form of research based on human understanding and behavior based on human opinion, and the research subjects can be individuals or groups.